2017
DOI: 10.1038/ni.3813
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1-dependent nanoscale organization of the BCR regulates B cell tolerance

Abstract: Caveolin-1 (Cav1) regulates the nanoscale organization and compartmentalization of the plasma membrane. Here we found that Cav1 controlled the distribution of nanoclusters of isotype-specific B cell antigen receptors (BCRs) on the surface of B cells. In mature B cells stimulated with antigen, the immunoglobulin M BCR (IgM-BCR) gained access to lipid domains enriched for GM1 glycolipids, by a process that was dependent on the phosphorylation of Cav1 by the Src family of kinases. Antigen-induced reorganization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 52 publications
2
59
0
1
Order By: Relevance
“…These IgM and IgD type BCRs possess identical antigen‐binding sites, but differ in their membrane‐bound heavy chain isoforms. GM1‐enriched membrane lipid rafts involved in BCR signaling may be responsible for the ganglioside‐related immune functions of B lymphocytes . IgM‐BCR is not closely localized to GM1‐enriched lipid rafts in resting B cells, whereas IgD‐BCR is located adjacent to these lipid domains .…”
Section: Gangliosides In Adaptive Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…These IgM and IgD type BCRs possess identical antigen‐binding sites, but differ in their membrane‐bound heavy chain isoforms. GM1‐enriched membrane lipid rafts involved in BCR signaling may be responsible for the ganglioside‐related immune functions of B lymphocytes . IgM‐BCR is not closely localized to GM1‐enriched lipid rafts in resting B cells, whereas IgD‐BCR is located adjacent to these lipid domains .…”
Section: Gangliosides In Adaptive Immunitymentioning
confidence: 99%
“…IgM‐BCR is not closely localized to GM1‐enriched lipid rafts in resting B cells, whereas IgD‐BCR is located adjacent to these lipid domains . BCR stimulation induces the translocation of IgM‐BCRs into GM1‐enriched lipid rafts in a caveolin‐1‐dependent manner, whereas IgD‐BCRs are excluded from these lipid domains , resulting in the clustering of IgM‐ and IgD‐BCR nanoclusters. The mechanisms by which IgM and IgD nanoclusters are organized in GM1‐enriched lipid rafts and modulate BCR signaling remain unknown.…”
Section: Gangliosides In Adaptive Immunitymentioning
confidence: 99%
“…We next examined the role of LAPF in caveolae formation. It has been reported that Cav1 can be phosphorylated by the tyrosine kinase Src and that activated Cav1 promotes caveolae-mediated endocytosis (27,28). On the other hand, Cav2 could not be phosphorylated by Src (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, different subsets of leukocytes derived from CAV1-null mice have been analyzed in terms of response to either parasitic [ 46 ] or bacterial infection [ 27 ]. Also, the ability of lymphocytes from CAV1-null mice to induce a humoral [ 47 ] or cytotoxic immune response [ 48 ] has been reported. However, studies have not focused on systemic inflammation in the absence of immune triggers.…”
Section: Discussionmentioning
confidence: 99%